Tamarindus indica Seed Extract-Based Botanical Compositions Alleviate Knee Pain and Improve Joint Function in Mild-to-Moderate Osteoarthritis: A Randomized, Double-Blind, Placebo-Controlled Clinical Study. (19th January 2022) - Kare, Sanjeev Kumar; Vinay, Vineet; Maresz, Katarzyna; Prisk, Victor; Vik, Hogne
Abstract : Objective . Knee pain and reduced joint function affect the quality of life of subjects suffering from knee osteoarthritis (KOA). The present randomized, double-blind, placebo-controlled study aimed to assess the clinical efficacy of two botanical compositions, NXT15906F6 and NXT19185, in pain relief and improvement in the musculoskeletal function of knee osteoarthritis (KOA) subjects. NXT15906F6 contains ethanol/aqueous extract of Tamarindus indica seeds and aqueous ethanol extract of Curcuma longa rhizome, and NXT19185 is a combination of NXT15906F6 and an aqueous ethanol extract of Garcinia mangostana fruit rind. Methods . The present trial recruited ninety subjects with mild-to-moderate KOA, using a radiographic Kellgren–Lawrence (KL) grading system. The participants were randomized into one of three groups ( n  = 30) to receive either placebo, NXT15906F6 (250 mg/day), or NXT19185 (300 mg/day) for 56 days. The change in Western Ontario and McMaster Universities Arthritis Index (WOMAC) score was the primary efficacy measure of the study. Improvements in the functional scores, serum proinflammatory modulators, and cartilage degradation product in the urine samples were the secondary efficacy measures. Twenty-seven subjects in each group completed the trial. Results . After the trial, NXT15906F6 and NXT19185 significantly improved P < 0.05 the WOMAC scores from baseline compared with placebo. In the subgroup analyses, the knee pain and functional scores were significantly improved in the KL-II and KL-III grade KOA subjects. At the end of the study, the NXT15906F6- and NXT19185-supplemented participants showed significant P < 0.05 improvement in the functional scores, inflammatory status, and collagen breakdown product in the urine samples. Summary. The present study demonstrates that NXT15906F6 and NXT19185 supplementations reduce knee pain and improve the musculoskeletal function of KOA subjects. Moreover, these herbal compositions helped reduce inflammation and inflammation-induced cartilage degeneration in the participants. NXT15906F6 and NXT19185 supplementations are further documented to be tolerable and safe to the participants.